315-(x+17)=115. Tìm x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. x - 17 = 115
x = 115 + 17
x = 132
b. 315 + ( 146 - x ) = 401
146 - x = 401 - 315
146 - x = 86
x = 60
a) ( x-47) - 115=0
x - 47 = 0 + 115 = 115
x= 115 + 47 = 162
b) 315 + ( 146 -x ) = 401
146 - x = 401 - 315 = 86
x= 146 -86 =60
a) \(\left(x-47\right)-115=0\)
\(x-47=115\)
\(x=115+47\)
\(x=162\)
b)\(315+\left(146-x\right)=401\)
\(146-x=401-315\)
\(146-x=56\)
\(x=146-56\)
\(x=90\)
a ) ( x - 47 ) - 115 = 0
( x - 47 ) = 0 + 115
( x - 47 ) = 115
x = 115 + 47
x = 162
b ) 315 + ( 146 - x ) = 401
( 146 - x ) = 401 - 315
( 146 - x ) = 86
x = 146 - 86
x = 60
Duyệt nha
a,(x-47)-115=0
x-47=115
x=162
b,315+(146-x)=401
315+146-x=401
461-x=401
x=60
a) (x - 47) - 115 = 0
=> x - 47 = 0 + 115
=> x - 47 = 115
=> x = 115 + 47
=> x = 162
Vậy x = 162
b) 315 + (146 - x) = 401
=> 146 - x = 401 - 315
=> 146 - x = 86
=> x = 146 - 86
=> x = 60
Vậy x = 60
3) 5.(x-15)-75=0
5.(x-15)=75
x-15=15
x=15+15
x=30
8) 315+(146-x)=491
146-x=491-315
146-x=176
x=146-176
x=-30
6) 6.x-5=600+13
6.x-5=613
6.x=613+5
6.x=618
x=618:6
x=103
11)(x-17):8+52=158
(x-17):8=158-52
(x-17):8=106
x-17=106.8
x-17=848
x=848+17
x=865
7) (x-47).5-115=0
(x-47).5=115
x-47=115:5
x-47=23
x=23+47
x=70
10) 135-5.(x+37)=80
5.(x+37)=135-80
5(x+37)=55
x+37=55:5
x+37=11
x=11-37
x=26
13) 320:y-10=5.48:24
320:y-10=240:24
320:y-10=10
320:y=10+10
320:y=20
y=320:20
y=16
a) (x - 47) - 115 = 0
\(\Rightarrow\)x - 47 - 115 = 0
\(\Rightarrow\)x - 162 = 0
\(\Rightarrow\)x = 0 + 162 = 162
Vậy giá trị của x là 162
b) 315 + (146 - x) = 401
\(\Rightarrow\)146 - x = 401 - 315 = 86
\(\Rightarrow\)x = 146 - 86 = 60
Vậy giá trị của x là 60
a.2436 :x = 12
x = 2436 : 12
x = 203
b. 6x - 5 = 613
6x = 613 + 5
6x = 618
x = 618 : 6
x = 13
c.( x - 47 ) - 115 = 7
x - 47 = 7 + 115
x - 47 = 122
x = 122 + 47
x =169
d . 315 + (146 - x ) =401
146 - x = 401 - 315
146 - x = 86
x = 146 - 86
x = 60
e.( x - 36 ) : 18 = 12
x - 36 = 12 x 18
x - 36 = 216
x = 216 + 36
x = 252
a , 2 436 : x = 12
x = 2 436 : 12
x = 203
b , 6x - 5 = 613
6x = 618
x = 103
c , ( x - 47 ) - 115 = 7
x - 47 = 122
x = 169
d , 315 + ( 146 - x ) = 401
146 - x = 401 - 315
146 - x = 86
x = 146 - 86
x = 60
e , ( x - 36 ) : 18 = 12
x - 36 = 216
x = 216 + 36
x = 252
315-(x+17)=115
x+17=315-115
x+17=200
x=200-17
x=183